IoT Based UV C Baby Equipment Sterilization System With Sensor Monitoring: Sistem Sterilisasi Peralatan Bayi Berbasis IoT dengan Sinar UV-C dan Pemantauan Sensor - Muhammad Riko; Akhmad Ahfas (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Hygiene of baby feeding equipment is essential due to infants’ low immunity and high risk of bacterial contamination. Specific Background: Conventional cleaning and drying methods are often ineffective and less hygienic, while existing sterilization systems lack integrated remote monitoring. Knowledge Gap: Previous studies have not fully integrated UV-C sterilization, heating-based drying, and Internet of Things control in a single system. Aims: This study aims to develop an IoT-based UV-C sterilization device using ESP32 to monitor and control sterilization and drying processes. Results: The drying system reduced moisture to a completely dry state, while sterilization testing showed bacterial counts below SNI thresholds. The IoT system operated up to 60.2 km with an average delay of 4.86 seconds, and the DS18B20 sensor achieved an average error of 0.25°C. Novelty: The integration of UV-C sterilization, heating drying, and long-distance IoT control with real-time monitoring represents the main contribution. Implications: This system provides a practical and hygienic solution for maintaining baby equipment cleanliness with reliable remote operation Keywords: Uv C Sterilization, Internet of Things, Esp32, Baby Equipment, Temperature Sensor Key Findings Highlights Drying process achieves complete moisture removal after extended duration Bacterial testing confirms compliance with microbiological safety standards Remote operation remains stable across multiple long-distance locations